GC-MS Profiling, In Vitro Antimalarial, and Antimicrobial activity of Ricinodendron heudelotii Seed Extracts - Imieje, Vincent Oghenerobo; Amafili, Lilian Nneoma (Sciences of Phytochemistry, 2025)
Malaria remains a significant public health challenge, particularly in sub-Saharan Africa, where the emergence of Plasmodium falciparum strains resistant to artemisinin-based combination therapies (ACTs) exacerbates the situation. This underscores the urgent need to identify novel, less toxic antimalarial compounds, particularly from natural sources. This study evaluated the in vitro antimalarial and antimicrobial activities of Ricinodendron heudelotii (RHD) seed extracts against Plasmodium falciparum (P. falciparum) and select pathogenic microorganisms using standard protocols. Seeds (250 g) were dried, ground, and extracted with n-hexane and dichloromethane, yielding RHD-HEX and RHD-DCM extracts, respectively. The oily extract (RHD-HEX) was analyzed via gas chromatography-mass spectrometry (GC-MS), revealing 26 phytoconstituents, including monoterpenes, fatty acids, and phytosterols. Antimalarial assays showed that RHD-HEX and RHD-DCM exhibited moderate activity (> 200 µg/mL) against the chloroquine-sensitive P. falciparum (D6 strain). Both extracts demonstrated stronger activity against the chloroquine-resistant W2 strain, with IC50 values of 30.29 and 33.48 µg/mL, respectively. Antimicrobial screening indicated moderate activity against tested pathogenic fungi and bacteria (IC50 > 200 µg/mL) compared to fluconazole and cefotaxime controls. Cytotoxicity against VERO cell lines was also assessed. The findings suggest that the phytoconstituents in RHD extracts may contribute to the observed antimalarial and antimicrobial effects, warranting further investigation.